Developing a Tool to Assess Students’ Views of Nature of Science in Vietnam - Yuenyong, C.; Thao-Do, T. P. (Jurnal Pendidikan IPA Indonesia, 2020)
Nature of Science (NOS) is a common topic in science education nowadays. However, the fact of the nature of science is not consensus through documents. The assessment of views of nature of science, therefore, was facing multi issues. Especially, in assessing views of NOS in a new context other than from where a validated tool was developed. Researchers and educators should notice certain issues relating to NOS. This paper will provide and discuss how to develop a more appropriate NOS tool to best use for Vietnamese Physics student teachers based on some previously validated tools and the empirical data from the research on the context. Instead of using a provided tool robotically, the paper calls for more critical employment of the tool based on the consideration of social and cultural context. This is not only important in the case of Vietnam but also any new circumstance.Ã‚Â